The potential of duck egg white as a modifier for activated rice straw to enhance Cr(VI) ions adsorption in an aqueous solution - Adewirli Putra; Syiffa Fauzia; Deswati Deswati; Syukri Arief; Rahmiana Zein (South African Journal of Chemical Engineering, 2024)
In this study, activated rice straw modified with duck egg white (RSA-DEW) was tested extensively to increase the adsorption capacity of Cr(VI) ions. The parametric study was carried out in a batch system, and the results showed that the maximum adsorption capacity of Cr(VI) ions using RSA-DEW was 94.904 mg g−1, far greater than using RSA of 60.204 mg g−1, in studies that have been reported. This optimum condition was achieved at pH 2, initial concentration of Cr(VI) 1000 mg L−1, contact time 30 min, particle size ≤ 36 µm, and stirring speed 100 rpm at 298 K. The principle of equilibrium follows the Freundlich isotherm model, which shows a multilayer adsorption process. Meanwhile, the adsorption kinetics follows a pseudo-second-order model, which indicates a chemical interaction between the adsorbent and the adsorbate. The thermodynamic evaluation showed that the adsorption of Cr(VI) ions onto RSA-DEW was exothermic and spontaneous. Prediction Adsorption mechanisms include pore filling, electrostatic interactions, reduction, ion exchange, and complexing. After five adsorption-desorption cycles were carried out to evaluate the reusability of the adsorbent, the efficiency of RSA-DEW did not change significantly, indicating good reusability. The application of RSA-DEW succeeded in removing Cr(VI) ions from river water contaminated with Cr(VI) ions, with a removal efficiency of up to 100 %. In conclusion, the novelty of this study presents the selection of Duck Egg White (DEW) as a new effective, low cost and advantageous modifier for removing Cr(VI) ions in solution.